Delftse Kunstenaars. - Stedelijk Museum "Het Prinsenhof", Delft (Delft : museum "Het Prinsenhof", 1972)
Van Den Berselaar, Harri ; Boekhorst-Froger, Claartje ; Van Bokhoven, Ton ; De Boon, Frederik W.J. ; Van Boshuysen May, R.D. ; Bouwer, Henk ; Van Breemen, Marloes ; Broer-Tertoolen, Ellis ; De Bruin, Ton ; Buter, Mieke en Ernst ; Bijsterveld, Johan ; Dam, Cor ; Derwort, H.J.L. ; Diehl, Gerard ; Douma, Jan Ernst ; Dukker, Hans ; etc.
Delftse Kunstenaars, Stedelijk Museum 'Het Prinsenhof', Delft, 22 december 1972 - 4 februari 1973
boek